Effects of Oleuropein and Hydroxytyrosol on Inflammatory Mediators: Consequences on Inflammaging - Pojero, Fanny; Aiello, Anna; Gervasi, Francesco; Caruso, Calogero; Ligotti, Mattia Emanuela; Calabrò, Anna; Procopio, Antonio; Candore, Giuseppina; Accardi, Giulia; Allegra, Mario (International journal of molecular sciences, 2022)
Aging is associated with a low-grade, systemic inflammatory state defined as “inflammaging”, ruled by the loss of proper regulation of the immune system leading to the accumulation of pro-inflammatory mediators. Such a condition is closely connected to an increased risk of developing chronic diseases. A number of studies demonstrate that olive oil phenolic compound oleuropein and its derivative hydroxytyrosol contribute to modulating tissue inflammation and oxidative stress, thus becoming attractive potential candidates to be used in the context of nutraceutical interventions, in order to ameliorate systemic inflammation in aging subjects. In this review, we aim to summarize the available data about the anti-inflammatory properties of oleuropein and hydroxytyrosol, discussing them in the light of molecular pathways involved in the synthesis and release of inflammatory mediators in inflammaging.